Self-Efficacy and Smoking Cessation: A Mixed Method Study among Adult Smokers in Fiji - Mohammadnezhad Masoud; Kengganpanich Mondha; Khan Sabiha; Makutu Litia; Mangum Tamara (Journal of Public Health International, 2023)
A mixed‑methods study examines self‑efficacy in smoking cessation among Fijian adults. It outlines qualitative themes and quantitative associations to guide tailored interventions.